2022
DOI: 10.1007/s12350-021-02678-8
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion recovery induced by an α-calcitonin gene-related peptide analogue

Abstract: Background Endogenous calcitonin gene-related peptide (CGRP) induces cardioprotective effects through coronary vasodilation. However, the systemic administration of CGRP induces peripheral vasodilation and positive chronotropic and inotropic effects. This study aims to examine the net effect on coronary perfusion of the systemically administered α-calcitonin gene-related peptide analogue, SAX, in rats during myocardial infarction. Methods Forty Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Next, Calu-3 cells were pre-treated for 24h at 37°C with CGRP within its concentration range that inhibits LCs-mediated HIV-1 and HSV-1/2 infection, as we reported (29,30). The cells were also pre-treated with the CGRP metabolically stable analogue SAX (serinyl-CGRP 2-37amide with an albumin binding fatty acid moiety in the N-terminus) that, like CGRP, exerts protective cardiovascular effects (37)(38)(39)(40) and anti-viral functions (29,30), as we reported. The cells were next washed, pulsed with SARS-CoV-2 variants for 4h, and infection was determined by flow cytometry as above.…”
Section: Cgrp and Its Analogue Sax Inhibit Sars-cov-2 Infection Of Ca...mentioning
confidence: 99%
“…Next, Calu-3 cells were pre-treated for 24h at 37°C with CGRP within its concentration range that inhibits LCs-mediated HIV-1 and HSV-1/2 infection, as we reported (29,30). The cells were also pre-treated with the CGRP metabolically stable analogue SAX (serinyl-CGRP 2-37amide with an albumin binding fatty acid moiety in the N-terminus) that, like CGRP, exerts protective cardiovascular effects (37)(38)(39)(40) and anti-viral functions (29,30), as we reported. The cells were next washed, pulsed with SARS-CoV-2 variants for 4h, and infection was determined by flow cytometry as above.…”
Section: Cgrp and Its Analogue Sax Inhibit Sars-cov-2 Infection Of Ca...mentioning
confidence: 99%
“…Researchers demonstrated that subcutaneous administration of acylated-α-CGRP significantly reduced cardiac hypertrophy, fibrosis, and inflammation, and improved cardiac function in these disease rodent models. Recently, the cardioprotective effect of a metabolically stable CGRP analog, SAX, has been tested in a constant left anterior descending (LAD) occlusion rat model of acute myocardial infarction (Bentsen et al, 2021). Researchers reported that intraperitoneal administration of SAX (100 nmole/kg bwt per rat) improved myocardial recovery after myocardial infarction.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%